Chemical and microbial evaluation of water of Rupa lake - Dhungana, Kamal Prasad; Mishra, Akkal Dev; Adhikari, Kalpana Gautam (BIBECHANA, 2023)
Analysis of chemical and microbial features of Rupa lake water was carried out in summer season by adopting accepted analytical techniques. Water samples were collected at 28°C, and on-site observations were made for features like colour, odour, pH, transparency, dissolved oxygen, and free carbon dioxide. In the laboratory, the concentration of prominent mineral ions and microbial contamination were measured using accepted analytical techniques. Transparency of lake water was noted 91cm and electrical conductivity 41 µs/cm indicating the presence of suspended particulate at moderately higher concentration. This water is slightly alkaline with pH of 7.2 that is accounted by domination of alkali and alkaline metal ions. Presence of nitrogenous species mainly ammonium and nitrate in excess amount has detected to be major reason for rapid eutrophication in the lake. Analysis of Rupa lake water has shown the considerable presence of phosphate and sulphate which have added to the hardness 130 mg/L of the water as well. On the top of this fairly higher concentration of free carbon dioxide indicates presence of organic wastes in association with decaying matters. Domestic sewage discharge, the use of pesticides and fertilizers in agricultural areas, as well as other solid waste dumps has caused microbial contamination and the biggest dangers to the viability of Rupa lake. The risk of contamination and the eutrophication process needs to be managed by creating public awareness [1].The study shows that water quality of Rupa lake is contaminated for drinking but adequately suitable for all aquatic life and ecological balance.